Investigations into the mechanical properties of insect cuticle - Parle, Eoin E. (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2016)
Insect cuticle is a composite material comprised of chitin fibres embedded in a protein matrix. It performs a wide variety of functions across class Insecta, and as such displays a wide bandwidth of material properties. This is achieved by varying the amounts and orientations of the fibres, the constituents of the proteins, and their degree of cross-linking and hydration. Many previous studies into the mechanical properties of insect cuticle have focussed on the insect tibia and have characterised such properties as strength, toughness, hardness, stiffness and fatigue. This Ph.D. builds on previous work by investigating how various tibia properties such as its geometry, its strength, stiffness and failure mode can be influenced by a number of different factors. I have examined insect cuticle from a fracture mechanics and material science point of view. In all studies, a cantilever bending load was applied to tibiae to replicate bending forces experienced in vivo. A sensitive 5 N load cell recorded applied force, and tibia dimensions were analysed using SEM photographs. From these reliable, repeatable calculations for stress, strain and stiffness were obtained. When investigating how biomechanical factors have influenced the adaptation of tibia cuticle in several different insect tibiae, I found that they must endure higher forces during emergency behaviour than during normal locomotion such as walking and running. Comparing the failure strengths of each leg with the stresses endured in vivo allowed me to estimate safety factors for each leg. These were relatively high (6 – 7) for normal locomotion, but much lower (1.5 – 4) for more strenuous activities. This implies that the legs operate close to their structural limit during such activities. I also found that the age of the adult locust can have a profound effect on the tibia properties. Its thickness increases at a rate of 1.8 μm / day for the first 20 days (approx.) after moulting, after which cuticle deposition rates reduce to approx. 0.4 μm / day. This is accompanied by a rapid increase in strength and stiffness over the same time period, after which both properties remain relatively constant. After moulting, and when the cuticle is thin (high radius / thickness ratio), the legs are inclined to fail by local buckling. This in itself is an incentive to grow thicker and become stiffer. Once the cuticle reaches a certain thickness, buckling is no longer the primary failure mode (as shown by the predictive calculations). The legs will now fail due to material failure (fracture / yielding). This is not a failure mode that can be avoided by the addition of more material, hence the significant decrease in deposition rate after this point. I have examined the phenomenon of local elastic buckling of the tibiae of several insect species including the desert locust hind-leg and mid-leg, the American and Death’s head cockroaches, the stick insect and the bumblebee using predictive equations from the literature and FE modelling. I found that such predictions matched my experimental results closely, implying that this type of analysis could prove useful for predicting failures of other insect tibiae in the future, or indeed thin-walled tubular structures of any kind – including those with a non-circular cross-section, or with specialisations such as ridges or fins seen on the stick insect. When examining how the insect responds to injury, I discovered the importance of the deposition of new cuticle underneath an incision in the repair process. This helps to reinforce the tibia structure, and restore its strength to acceptable levels. A tibia showing repair recovered on average 66% of its original pre-injury strength compared to the corresponding value of 33% for an injured leg showing no repair. This patch of new cuticle is also vital in preventing cracks from growing from the injury. I have confirmed that the deposition of new cuticle in response to injury is targeted to the injury site, and that the rate of deposition here closely matches that seen immediately post-moult. Deposition rates in other areas (including beside the injury) remained at normal levels for a mature adult – implying that the injury itself is a stimulus for the local resurrection of the accelerated growth rate observed after moulting. I also examined how the insect responds to minor or material level damage. I observed how the living cuticle can recover completely from high stress cyclic loading, regaining its stiffness completely, and showing no difference in failure strength or stiffness to legs (from the same insects) which had not been cycled. Tibiae removed from the insect showed no such recovery, implying that the processes at work may be governed by the living cells of the insect as opposed to being a passive material phenomenon. I have detailed all of the above in this thesis, and have proposed possible theories explaining the behaviours observed. The more studies carried out on this interesting material, the more thought-provoking results are discovered. I believe that this thesis has shed some light on various factors that influence the mechanical properties of insect cuticle, and together with previous work, goes some way to building a more complete understanding of this versatile material.
Keywords: Mechanical and Manufacturing Engineering, Ph.D.; Ph.D. Trinity College Dublin